Sosialisasi Penerapan Educaplay Sebagai Pendukung Pembelajaran Joyfull Learning Bagi Guru Di SD Muhammadiyah Purworejo - Titi Anjarini; Aci Primartadi; Suyoto; Arum Ratnaningsih; Rintis Rizkia Pangestika; Fasya Mauludiana (Jurnal Pengabdian kepada Masyarakat Radisi, 2026)
The use of interactive digital learning media in elementary schools is still not optimal, so learning tends to take place conventionally and does not create a fun learning atmosphere. This condition is also found among teachers at Muhammadiyah Elementary School in Purworejo, who still have limitations in understanding the concept of fun learning and utilizing game-based learning platforms. This community service activity aims to improve teachers' knowledge and skills in implementing Educaplay as a support for fun learning. The methods used include needs observation, socialization, training, demonstrations, direct practice, mentoring, and evaluation using questionnaires before and after the activity. The activity was attended by nine teachers at Muhammadiyah Elementary School in Purworejo. The results of the activity showed an increase in teacher competency across all measured indicators. The average understanding of the concept of fun learning increased from 1.56 to 3.78, understanding of the function of Educaplay as an interactive learning medium reached an average of 3.67, the ability to create interactive quizzes increased from 1.78 to 3.89, insight into digital learning media increased to 3.78, while ease of understanding the material obtained an average of 3.83. All indicators were in the very good category after the implementation of the activity. Thus, the socialization and training of Educaplay implementation has proven effective in improving teacher competence in developing interactive digital learning media, thereby supporting the creation of fun, innovative, and student-centered learning in elementary schools.